The immunoregulatory function of peripheral blood CD71+ erythroid cells in systemic-onset juvenile idiopathic arthritis - Hikaru Kanemasa (Nature Portfolio, 2021)
Abstract CD71+ erythroid cells (CECs) are recognized to have an immunoregulatory function via direct cell–cell interaction and soluble mediators. Circulating CECs appear in newborns or patients with hemolytic and cardiopulmonary disorders. To assess the biological role of CECs in systemic inflammation, we studied the gene expression and function in systemic-onset juvenile idiopathic arthritis (SoJIA). Peripheral blood mononuclear cells of SoJIA patients expressed upregulated erythropoiesis-related genes. It represented the largest expansion of CECs during active phase SoJIA among other inflammatory diseases. Despite the opposing roles of erythropoietin and hepcidin in erythropoiesis, both serum levels were in concert with the amounts of SoJIA-driven CECs. Circulating CECs counts in inflammatory diseases were positively correlated with the levels of C-reactive protein, IL-6, IL-18, or soluble TNF receptors. Co-culture with active SoJIA-driven CECs suppressed secretions of IL-1β, IL-6, and IL-8 from healthy donor monocytes. The top upregulated gene in SoJIA-driven CECs was ARG2 compared with CECs from cord blood controls, although cytokine production from monocytes was suppressed by co-culture, even with an arginase inhibitor. CECs are driven to the periphery during the acute phase of SoJIA at higher levels than other inflammatory diseases. Circulating CECs may control excessive inflammation via the immunoregulatory pathways, partly involving arginase-2.